KOMPETENSI KEPALA SEKOLAH DALAM MEMBANGUN SEKOLAH EFEKTIF - Rayendra Rayendra; Mutiara Felicita Amsal (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2018)
Effective schools are schools that demonstrate high standards on academic and non-academic achievement and have a culture that is oriented towards the goals to be achieved and this is marked by the formulation of a vision that is established and promoted jointly between school residents consisting of principals, teachers, staff, other employees, school committees, students, and other stakeholders. The quality of school leaders is one of the basic factors that influence the quality of the teaching and learning process significantly at every level of the education system. Competencies that must be possessed by effective principals are 1) interpersonal and communication skills, 2) It is important that principals master the transformation of technology-based education; 3) Competency in the field of management manages the development of schools as an institution that manages human resources.Keyword: Principal, Effective Schools